Modelling and visualization of the White Stork’s migration - Gliožerytė , Dominyka; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2008)
The aim of this article is to present a computational modelling of the White Stork’s migration. The transfer equation is proposed and applied to describe the migration of White Stork.